Indian currency and finance - Keynes, John Maynard (Jaipur: HillTop, 2023)
Keynes first published work on economics. In Indian Currency and finance , Keynes argued for the adoption of the gold exchange standard rather than the full gold standard.
Includes bibliographical references.
Keywords: Currency question -- India; Banks and banking -- India